Kasus Tuberkulosis Paru dengan Stunting pada An.Sw dengan Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Sindang Jaya - Eunike Alicia Valentina; Rayhan Al-ghifari Iridansyah Siregar; Hania Angelia; Tom Surjadi (Malahayati Nursing Journal, 2023)
ABSTRACT Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis.The highest mortality occurs in children aged under five years old, particularly those who are malnourished. In 2021, Indonesia is ranked second for country with the highest TB incidence, with a total of 42.187 TB cases in children. Stunting is a chronic nutritional problem caused by malnutrition and recurrent infection, especially in the first thousand days of life. Stunting inhibits physical growth, increasing susceptibility to disease, and interferes with child cognitive development, thereby reducing child’s intelligence and productivity in the future. Studi Status Gizi Indonesia (SSGI) 2021 showed that the prevalence of stunting in Indonesia is 24,4%, which is still considered high. Family medicine approach to increase growth and development, treat and prevent infection, prevent cognitive impairment of An. SW in the future. This research utilized a qualitative approach with a case study research design. The case in this study is a 14-month-old female toddler with the initials SW who presented with recurrent acute respiratory infections. An. SW was born prematurely with low birth weight and her mother was a 16-year-old teenager. Upon conducting an anthropometric examination, An. SW was found to be severely stunted. Holistic and comprehensive treatment has been done to An. SW, so that her complaints are reduced, her weight is increasing, and now she has received adequate treatment for pulmonary tuberculosis with her mom as supervisor. The family of An. SW has understood about stunting and lung tuberculosis and also has improved their parenting style, especially in terms of feeding practices. It was found that the stunting in An. SW was caused by infectious factor such as, lung tuberculosis and non-infectious factors such as inadequate nutrition intake and the parents’ lack of knowledge. After the family medicine approach, the weight of An. SW is increasing and she finally gets the antituberculosis drugs. Keywords: Pulmonary Tuberculosis, Stunting, Family Medicine  ABSTRAK Tuberkulosis (TB) adalah penyakit yang disebabkan oleh infeksi bakteri Mycobacterium tuberculosis. Mortalitas tertinggi terjadi pada anak di bawah usia 5 tahun, terutama pada anak-anak dengan malnutrisi. Pada tahun 2021, Indonesia menduduki peringkat kedua angka kejadian TB tertinggi dengan jumlah kasus TB anak sebanyak 42.187 kasus. Stunting adalah masalah gizi kronis yang terjadi akibat malnutrisi dan infeksi berulang pada 1.000 Hari Pertama Kehidupan. Stunting menghambat pertumbuhan fisik, menyebabkan anak rentan terhadap penyakit dan mengganggu perkembangan kognitif anak sehingga menurunkan tingkat kecerdasan dan produktivitas anak di masa depan. Studi Status Gizi Indonesia (SSGI) 2021 menunjukkan bahwa prevalensi stunting di Indonesia masih tergolong tinggi, yaitu 24,4%. Kunjungan kedokteran keluarga untuk meningkatkan tumbuh kembang, mengatasi dan mencegah infeksi, serta mencegah gangguan kognitif di masa depan pada An. SW. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Adapun kasus dalam penlitian ini yaitu Seorang balita perempuan beinisial SW dan berusia 14 bulan datang dengan keluhan ISPA berulang. An. SW terlahir prematur dengan BBLSR dan ibunya adalah remaja berusia 16 tahun. Saat dilakukan pemeriksaan antropometri, An. SW tergolong severely stunted. Tata laksana holistik dan komprehensif telah dilakukan sehingga keluhan An. SW berkurang, berat badannya meningkat, dan saat ini telah mendapatkan pengobatan TB paru yang adekuat dengan ibunya sebagai PMO. Keluarga telah memahami tentang stunting dan TB paru, serta memperbaiki pola asuh terutama dalam hal praktik pemberian makanan. Ditemukan bahwa kondisi stunting pada pasien disebabkan oleh faktor infeksi yaitu TB paru serta faktor non-infeksi kurangnya asupan gizi dan pengetahuan orang tua. Setelah dilakukan pendekatan kedokteran keluarga, berat badan An. SW meningkat dan telah mendapatkan OAT. Kata Kunci: Tuberkulosis Paru, Stunting, Kedokteran Keluarga.